Self-healing key distribution scheme of MANET based on sliding window - DU Chun-lai; HU Ming-zeng; ZHANG Hong-li; ZHANG Wei-zhe (Tongxin xuebao)
A new self-healing key distribution scheme of MANET based on sliding window was proposed in order to re-duce the burden of manager supervising self-healing MANET and to deal with the scene of some users’ lifetime bestrid-ing two session windows.A dual hash directional key chain model was set up.The model achieves t-revocation capability by using control parameter.Through the security analysis,the model has settled users’ bestriding problem yet still achieved security property.Because manager once distributes initial private information to bestriding user and so avoids distributing it again in rebuilding phase,the model reduces the communication cost.